Analisis Kompetensi Guru Ditinjau Dari Kepemimpinan Kepala Sekolah Dan Kompensasi - Endra Kristiani (Universitas Islam Kadiri, 2020)
Competencies possessed by teachers are expected to carry out their duties as professional teachers, and help to educate the nation's children, and improve the quality or quality of education in Indonesia. This study aims to find out significantly the effect of Principal Leadership and Compensation on Teacher Competence in Junior High School 3 Blitar. This research uses quantitative research methods with a population of 60 teachers in Junior High School 3 Blitar as respondents. The research variables consisted of independent variables, namely the principal's leadership and compensation and the dependent variable was teacher's competence. Data collection using a questionnaire measured by a 5 level linkert scale. The analysis tool uses multiple linear regression. The results of the study indicate that there is influence both partially and simultaneously the leadership of the principal and compensation for teacher competence.